(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Various interpretations of the content-language integrated approach (CLIL) are presented in this article, along with its varieties, opportunities, and features of implementation in bilingual education through the application of its basic principles and strategies. The CLIL is currently characterised in the world scientific and methodological literature as one of the innovative approaches to the organisation of bilingual education and involves the implementation of two learning goals in two subject areas: language and subject